Speculation : politics, ideology, event - Daly, Glyn (Diaeresis., 2019)
Speculation: Politics, Ideology, Event develops Hegel's radical perspective of speculative thought as a way of reclaiming and revitalizing the sense of the future and its possibilities. Engaging with such figures as Alain Badiou, Quentin Meillassoux, Ernesto Laclau, Slavoj Žižek, and Fredric Jameson, Glyn Daly articulates the distinctness of speculative philosophy and draws its implications for new debates in areas of science, politics, capitalism, ideology, ethics, and the event. In a confrontation with today's fatalistic milieu, principal emphasis is given to Hegel's idea of infinity as the intrinsic dimension of negativity within all finitude. Against the modern era's paradigmatic tendency to externalize social problems in the form of antagonism and Otherness, Daly argues for a renewal of utopian thought based on Hegelian reconciliation and the affirmation of excess as the essence of all being. On these grounds, he advances a new kind of political imagination that in speculative terms centers on uncompromising notions of truth and reason.